2022
DOI: 10.3390/life12030399
|View full text |Cite
|
Sign up to set email alerts
|

Application of Orthobiologics in Achilles Tendinopathy: A Review

Abstract: Orthobiologics are biological materials that are intended for the regeneration of bone, cartilage, and soft tissues. In this review, we discuss the application of orthobiologics in Achilles tendinopathy, more specifically. We explain the concepts and definitions of each orthobiologic and the literature regarding its use in tendon disorders. The biological potential of these materials can be harnessed and administered into injured tissues, particularly in areas where standard healing is disrupted, a typical fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 155 publications
(177 reference statements)
0
8
0
Order By: Relevance
“…However, these same cells also produce matrix metalloproteinases which degrade the NP ECM. The presence of anabolic signals such as IGF-1, TGF and bFGF promotes ECM deposition [16], whereas various inflammatory cytokines (typically secreted following tissue injury promote ECM degradation [8,9,[17][18][19][20]. Therefore, if the cellular microenvironment shifts IVD cells to a catabolic state, degradation of the NP matrix will begin [21].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…However, these same cells also produce matrix metalloproteinases which degrade the NP ECM. The presence of anabolic signals such as IGF-1, TGF and bFGF promotes ECM deposition [16], whereas various inflammatory cytokines (typically secreted following tissue injury promote ECM degradation [8,9,[17][18][19][20]. Therefore, if the cellular microenvironment shifts IVD cells to a catabolic state, degradation of the NP matrix will begin [21].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Some of the most popular contemporary orthobiologic alternatives commercially available are autologous solutions such as platelet-rich plasma (PRP), bone marrowderived products and adipose tissue derivatives [8]. These materials trigger a wide set of biological responses that contribute to the amelioration of regeneration in areas where standard tissue healing is disrupted or difficult to achieve [9]. Although the biological mechanisms are complex, the aforementioned products share many similarities, especially in virtue of autocrine and paracrine signaling via release of several bioactive molecules [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ectopic but ADSCs induce neovascularization and inhibit inflammation in the early phase of tendon injury, so demonstrated as the best source for tendon repair (Ramires et al, 2022).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…OA, for instance, remains the utmost typical degenerative and progressive joint disease affecting vital musculoskeletal (MSK) structures like cartilage, ligaments, and bone. 7,8 Furthermore, the Global Burden of Disease Study 2019 revealed that the number of patients suffering from OA increased globally around 48% from 1990 to 2019, which represents OA as 15th most common cause of number of years lived with disability. 9 This fact is associated with risk factors like the aging and the prevalence of poor metabolic health, especially the obesity.…”
Section: Introductionmentioning
confidence: 99%